Additive contribution of microRNA-34a/b/c to human arterial ageing and atherosclerosis. (June 2021) - Gatsiou, Aikaterini; Georgiopoulos, Georgios; Vlachogiannis, Nikolaos I.; Pfisterer, Larissa; Fischer, Ariane; Sachse, Marco; Laina, Ageliki; Bonini, Francesca; Delialis, Dimitrios; Tual-Chalot, Simon; Zormpas, Eleftherios; Achangwa, Rawlings; et al.
Abstract: Background and aims: Preclinical data suggest that the ageing-induced miR-34a regulates vascular senescence. Herein we sought to assess whether the miR-34 family members miR-34a, miR-34b and miR-34c are involved in human arterial disease. Methods: Expression levels of miR-34a/b/c were quantified by TaqMan assay in peripheral blood mononuclear cells (PBMCs) derived from a consecutive cohort of 221 subjects who underwent cardiovascular risk assessment and thorough vascular examination for aortic stiffness and extent of arterial atherosclerosis. Results: High miR-34a was independently associated with the presence of CAD [OR (95%C.I.): 3.87 (1.56–9.56); p  = 0.003] and high miR-34c with the number of diseased arterial beds [OR (95%C.I.): 1.88 (1.034–3.41); p  = 0.038], while concurrent high expression of miR-34-a/c or all three miR-34a/b/c was associated with aortic stiffening (miR-34a/c: p  = 0.022; miR-34a/b/c: p  = 0.041) and with the extent of atherosclerosis [OR (95%C.I.) for number of coronary arteries [miR-34a/c: 3.29 (1.085–9.95); miR-34a/b/c: 6.06 (1.74–21.2)] and number of diseased arterial beds [miR-34a/c: 3.51 (1.45–8.52); miR-34a/b/c: 2.89 (1.05–7.92)] after controlling for possible confounders ( p  < 0.05 for all). Mechanistically, the increased levels of miR-34a or miR-34c were inversely associated with expression of SIRT1 or JAG1, NOTCH2, CTNNB1 and ATF1, respectively. The association of miR-34a/c or miR-34a/b/c with CAD was mainly mediated through SIRT1 and to a lesser extent through JAG1 as revealed by generalized structural equation modeling. Leukocyte-specific ablation of miR-34a/b/c ameliorates atherosclerotic plaque development and increases Sirt1 and Jag1 expression in an atherosclerosis mouse model confirming the human findings. Conclusions: The present study reveals the clinical significance of the additive role of miR-34a/b/c in vascular ageing and atherosclerotic vascular disease. Graphical abstract: Image 1 Highlights: Increased levels of peripheral blood mononuclear cell (PBMC) miR-34a/b/c family members are associated with adverse cardiovascular risk profile. The concurrent increase of PBMC miR-34a/b/c is independently associated with aortic stiffness and presence and extent of human atherosclerosis. The miR-34 target SIRT1 is implicated in the miR-34a/b/c related effect in human atherosclerotic vascular disease. Leukocyte-specific ablation of  miR-34abc −/− attenuated atherosclerosis in mice.